Dynamic mechanical and thermal properties of Flax/bio-phenolic/epoxy reinforced hybrid composites - Ismail, Ahmad Safwan; Jawaid, Mohammad; Hamid, Norul Hisham; Yahaya, Ridwan; Sarmin, Siti Noorbaini; Fouad, Hassan; Sain, Mohini (Elsevier, 2023)
Objectives: The influence of flax fibre loading on the dynamic thermal and mechanical characteristics of composites was investigated in this work. Methods: Flax composites were fabricated at 30 (F-30), 40(F-40) and 50(F-50) wt% fibre loading. As a control, a bio-phenolic/epoxy polymer blend (P-20) containing 20% bio-phenolic was made. Results: The findings suggest that the incorporation of flax into the composites led to an enhancement in the dynamic mechanical properties of the experimental sample. The glass transition temperature (Tg) was identified via dynamic mechanical analysis to be between 60°C and 85 °C. Aside from that, the cole–cole plot revealed a heterogeneous mixture of fabricated samples, with strong fibre-to-matrix adhesion. Thermogravimetric analysis (TGA) showed adding flax to the composite reduces thermal stability. Conclusions: With the integration of flax as reinforcement, it could be asserted that the composites’ dynamic mechanical properties improved while their thermal stability reduced.